Fluorescence diagnosis and photodynamic therapy of skin cancer with alasens - S. V. Evstifeev; M. T. Kulaev; A. Z. Al’myashev; P. I. Skopin; I. V. Begoulov; O. A. Rybkina (Biomedical Photonics, 2014)
The results of treatment in patients with skin cancer using the method of photodynamic therapy (PDT) with alasens are represented in the article. The study enrolled 25 patients with stage 1 tumor including 23 patients with previously untreated tumors and 2 – with recurrent disease. Superficial tumor was diagnosed in 17 patients and 8 patients had nodal tumor. Alasens was used locally as application of 20% ointment on involved skin area with 6h exposure. The PDT session was performed on a single occasion immediately after the end of exposure (power density of laser irradiation of 50–100 mW/cm2, light dose – 150–200 J/cm2). All patients had fluorescence diagnosis (FD) prior to application of the ointment and before PDT. The results of FD showed that intensity of porphyrin fluorescence in tumor prior to administration of alasens had near no difference from intensity of porphyrin fluorescence in normal skin (12.5±0.7 and 10.0±0.7 r.u., respectively). Six hours after application of the ointment with alasens the fluorescence intensity of protoporphyrin IX increased almost 5-fold (59.7±5.3 r.u.), the fluorescence intensity in normal skin remained near baseline level during the follow-up period (maximally 11.6±1.0 r.u.). Two months after PDT the complete tumor regression was confirmed in 21 patients, partial – in 3 and stabilization of tumor growth in 1 patient. In addition, patients with superficial disease had complete regression in 94.1% of cases and partial regression in 5.9% while for patients with nodal tumor – 62.5% and 25%, respectively, stabilization – in 12.5%.